The Positive Youth Development and Career Adaptability on Undergraduate Students: Academic Achievement Moderated - Lubis, Rahmi; Amaliyana, Rizki (Kuras Institute, 2024)
Towards the completion of their tertiary education, students should have adapted to the work demands of the future. Career adaptability is determined by the student's character or personal assets. However, the influence of personal attributes on career adjustment is not always consistent. Other factors influence the strength of this influence. This research aims to determine the moderating role of academic achievement in the relationship between positive youth development (PYD) and student career adaptability. Data collection used the Positive Youth Development Scale and Career Adaptability Scale. We measured academic achievement using GPA. The research involved 286 eighth-semester students using a total sampling technique. Data analysis used a moderation test with Jamovi 2.0.0 statistical software. The results show that academic achievement moderates the impact of positive youth development on career adaptability. We found that PYD has a high effect on career adaptability in students with a high GPA. In contrast, PYD has low impact on career adaptability in students with low GPAs. The research results are beneficial in overcoming the low adaptability of students' careers by increasing positive youth development and academic achievement.